Introduction to General, Organic, and Biochemistry - Bettelheim, Frederick (Boston, Massachusetts : Brooks/Cole Publishing Company, 2010)
This text teaches the chemistry of the human body, and is intended for students entering the health sciences and related fields. In its entirety it can be used for a one year course in chemistry.
1. Matter, Energy and Measurement -- 2. Atoms -- 3. Nuclear Chemistry -- 4. Chemical Bonds -- 5. Chemical Reactions -- 6. Gases, Liquids, and Solids -- 7. Solutions and Colloids -- 8. Reaction Rates and Chemical Equilibrium -- 9. Acids and Bases -- 10. Organic Chemistry -- 11. Alkanes -- 12. Alkenes and Alkynes -- 13. Benzene and its Derivatives -- 14. Alcohols, Ethers, and Thiols -- 15. Chirality and the Handedness of Molecules -- 16. Amines -- 17. Aldehydes and Ketones -- 18. Carboxylic Acids -- 19. Carboxylic Esters, Amides and Anhydrides -- 20. Carbohydrates -- 21. Lipids -- 22. Proteins -- 23. Enzymes -- 24. Chemical Communications: Neurotransmitters and Hormones -- 25. Nucleotides, Nucleic Acids and Heredity -- 26. Gene Expression and Protein Synthesis -- 27. Bioenergetics: How the Body Converts Food to Energy -- 28. Specific Catabolic Pathways: Carbohydrate, Lipid, and Protein Metabolism -- 29. Biosynthetic Pathways -- 30. Nutrition -- 31. Immunochemistry -- 32. Blood Chemistry and Body Fluids (available on the web for custom publishing) -- Appendix I. Exponential Notation -- Appendix II. Significant Figures.
Includes index.
Keywords: CHEMISTRY -- TEXTBOOKS